2022
DOI: 10.1002/ski2.183
|View full text |Cite
|
Sign up to set email alerts
|

Nail involvement in patients with epidermolysis bullosa: A systematic review

Abstract: Background Nail changes in patients with congenital epidermolysis bullosa (EB) are caused by abnormalities of the nail matrix and bed secondary to pathogenic alterations of the dermoepidermal junction. Even though ungual alterations are extremely frequent in these patients, there are scarce studies about their frequency and/or association with subtypes or clinical course of EB. Objectives To systematically review nail abnormalities in patients with EB reported in the literature. Methods We searched all publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…A systematic review recently reported that the most common nail abnormalities in EB are dystrophic nails (48.6%), anonychia (43.2%) and pachyonychia (40.5%) with anonychia being correlated to multiple organ involvement and severe JEB (62.9%) or RDEB (50%) clinical subtypes. Similarly, abnormal nails were most commonly observed in DEB and JEB patients of our Middle Eastern cohort (approximately 85% of patients) and in only 20% of EBS and KEB patients 25 . Accordingly, nail changes in EB patients should be documented and followed since birth and they can predict EB subtype, severity, and extra‐cutaneous risk.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…A systematic review recently reported that the most common nail abnormalities in EB are dystrophic nails (48.6%), anonychia (43.2%) and pachyonychia (40.5%) with anonychia being correlated to multiple organ involvement and severe JEB (62.9%) or RDEB (50%) clinical subtypes. Similarly, abnormal nails were most commonly observed in DEB and JEB patients of our Middle Eastern cohort (approximately 85% of patients) and in only 20% of EBS and KEB patients 25 . Accordingly, nail changes in EB patients should be documented and followed since birth and they can predict EB subtype, severity, and extra‐cutaneous risk.…”
Section: Discussionmentioning
confidence: 75%
“…Nail abnormalities are common in EB and result from altered dermo-epidermal junction of the nail matrix, nail bed, proximal nail fold, and hyponichium. 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation